2014
DOI: 10.1097/md.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Association Between XPD Lys751Gln and Asp312Asn Polymorphisms and Hepatocellular Carcinoma Risk

Abstract: Genetic polymorphisms of xeroderma pigmentosum group D (XPD) in the nucleotide excision repair pathway may influence cancer susceptibility by affecting the capacity for DNA repair. Studies investigating the association between XPD Lys751Gln and Asp312Asn polymorphisms and hepatocellular carcinoma (HCC) risk reported inconsistent results. The aim of this study was to quantitatively summarize the evidence for such an association.Eligible studies were identified by searching electronic databases including PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…This suggests that genetic susceptibility resulting from XPD GSNPs might have a potential efect on AFB1-related HCC risk among Guangxiese population. Meta-analysis further improved the above-mentioned hypothesis [56]. However, the studies from molecular epidemiological studies exhibit that another GSNP of XPD is not signiicantly correlate with the risk of HCC related to AFB1 [49,58].…”
Section: Xeroderma Pigmentosum D (Xpd) Gsnps and Afb1-hcc Among Guangmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests that genetic susceptibility resulting from XPD GSNPs might have a potential efect on AFB1-related HCC risk among Guangxiese population. Meta-analysis further improved the above-mentioned hypothesis [56]. However, the studies from molecular epidemiological studies exhibit that another GSNP of XPD is not signiicantly correlate with the risk of HCC related to AFB1 [49,58].…”
Section: Xeroderma Pigmentosum D (Xpd) Gsnps and Afb1-hcc Among Guangmentioning
confidence: 96%
“…To date, molecular epidemiological studies on two GSNPs in this gene, namely, rs369191500 polymorphism (codon 312, Asp to Asn) and rs13181 polymorphism (codon 751, Lys to Gln), have been conducted by diferent laboratories [54]. Genotype-phenotype analyses have shown that these two GSNPs are associated with low DNA repair ability, which might modify DNA-adduct levels, p53 gene mutation, and risk of cancer [55,56]. For genetic polymorphisms among Guangxiese population, a total of four epidemiological studies have been conducted via case-control design ( [58].…”
Section: Xeroderma Pigmentosum D (Xpd) Gsnps and Afb1-hcc Among Guangmentioning
confidence: 99%
“…XPD polymorphisms or changes in XPD expression have been associated with a wide array of malignancies [ 3 , 11 – 18 ]. With specific respect to HCC, recent studies have tied several unique XPD polymorphisms (e.g., Lys751Gln, Arg399Gln, and Asp312Asn) to increased HCC susceptibility [ 3 5 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Cancer is a multifactor disease resulting from the combined effect of genetic susceptibility and environmental factors. 2 4 The role of inflammation in carcinogenesis is a pivotal issue. Previous studies have demonstrated that inflammation-associated molecules are associated with a majority of cancer types, and these molecules are activated by various elements related to environment and lifestyle.…”
Section: Introductionmentioning
confidence: 99%